The Prospect of Indonesian Knowledge-Based Economy: Lessons from Taiwan - Aryani, Maria Indira (Global and Policy Journal of International Relations, 2019)
ABSTRACTEconomic development is gradually shifting from a resource-based economy to investment-based economy to knowledge-based economy. Knowledge-bases economy is an economic process which concerns the creation, acquisition, dissemination and utilization of knowledge to achieve productivity. In utilizing knowledge, the economy would be more dependent towards information and technology. This paper is trying to see how knowledge-based economy is implemented in Indonesia by analyzing four pillars of education, innovation, information infrastructure and economic and institutional regime. The analysis of these four pillars can be put into SWOT assessment, combined with the assessment of Taiwan’s knowledge-based economy is used to see lessons that can be learned from Taiwan and opportunities that can further help Indonesia to achieve economic prosperity and equality. Taiwan as the first economy in Asia to have been successfully implementing the knowledge-based economy is the ideal role model for knowledge-based economy implementation.Keywords: Knowledge-based Economy, Indonesia, Taiwan, Four Pillars, SWOT Analysis DOI : https://doi.org/10.33005/jgp.v7i02.1835